Exploring science and history teachers' strategies in integrating tawheed at secondary school in Selangor : a case study - Hutapea, Riski Munandar (2018)
This study examines the teachers' strategies in integrating tawheed in teaching at al-Amin Islamic private secondary school in Selangor. The purpose of this study is to explore the teachers' perception of integrating tawheed in teaching, to find out the strategies that have been practiced by teachers in integrating tawheed in teaching and to find out the challenges that the teachers are facing in integration of tawheed in their teaching. The teachers were purposively selected based on their experiences in teaching. This research employed qualitative design by using case study. The methodological triangulation was used for collecting the data, and the data was collected from oral interviews and classroom observations. A total of 5 teachers from Al-Amin Islamic secondary school were selected to be interviewed and observed in classroom. The data was analysed using theme analysis. The data from the interviews and observations were transcribed and the key words were identified. Then, to start analysing the data, the researcher identified the theme and generated the sub-themes for further exploration. The findings showed that teachers' perceptions in integrating tawheed in teaching were important and it aimed to worship Allah. It has also been found that they implemented two strategies in integrating tawheed in teaching through teaching approaches and teaching methods. For teaching approaches, they used both deductive and inductive methods. Furthermore, for teaching methods, the teachers used story-telling, demonstrations and groups discussion to integrate tawheed in the lessons. However, the implementation of integrating tawheed in teaching in the classroom, all 5 teachers faced challenges either the challenges came from the teachers' self or came from school.